Analisis Pengaruh Sosialisasi Pajak, Kesadaran Wajib Pajak, dan Sanksi Pajak, Terhadap Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi dan Bangunan di Kelurahan Kabola Kecamatan Kabola Kabupaten Alor - Aneke Marta Waang (Peneliti.net, 2023)
Taxpayer compliance is an act of obedience and awareness of orderly payment and reporting of periodic and annual tax obligations from taxpayers in the form of a group of people and/or capital which is a business in accordance with applicable tax regulations. This study aims to determine the effect of tax socialization, tax payer awareness, and tax sanctions on taxpayer compliance in paying land and building taxes in Kabola Village, Kabola District, Alor Regency. This type of research is quantitative research with data collection techniques, namely observation, interviews, questionnaires and documentation studies. This study uses primary data. The population in this study is the community in Kabola Village, Kabola District, Alor Regency, totaling 1,162 people. And the sampling technique in this study is accidental sampling. Accidental sampling is a sampling technique based on coincidence, that is, anyone who happens to meet the researcher can be used as a sample, if it is deemed that the person met by chance is suitable as a data source. The respondents in this study were 60 people from the Kabola Village, Kabola District. , Alor Regency. The statistical method used in this study is multiple linear regression by looking at the significant value of the t test and the significant value of the F test as a benchmark in making hypotheses and the results of data management using the help of the IBM Spss 22 For Windows program. The results of this study indicate that: 1) partially the Tax Socialization variable has a significance value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the Tax Socialization variable partially has a positive effect on Taxpayer Compliance In Kabola Village, Kabola District, Alor Regency. 2) partially the Taxpayer Awareness variable has a significant value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the Taxpayer Awareness variable partially has a positive effect on Compliance Taxpayers in Kabola Village, Kabola District, Alor Regency. 3) partially the Tax Sanctions variable has a significant value of 0.003 or 0.3% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the Tax Sanctions variable has a partial positive effect on Taxpayer Compliance In Kabola Village, Kabola District, Alor Regency. 4) Simultaneously the variables of tax socialization, taxpayer awareness, and tax sanctions have a significant value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 which is 5% so that the results of this study simultaneously accept H4 which states that the variable tax socialization, taxpayer awareness, and tax sanctions have a positive effect on taxpayer